RELASI SOSIAL VIRTUAL SEBAGAI RUANG KOMUNIKASI POLITIK - Endang Dwi Sulistyoningsih (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2018)
Victory is the primary goal for eligible participants in legislative, regent, governor, and presidential elections. The use of social media became a means of garnering support from the public, but on the other hand openly getting attacks from supporters of the opposing camp. Mutual news